2008
DOI: 10.2337/dc07-1924
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence and Racial Differences in A1C Control

Abstract: OBJECTIVE -The purpose of this study was to examine medication adherence and other self-management practices as potential determinants of higher glycemic risk among black relative to white patients.RESEARCH DESIGN AND METHODS -We used a retrospective, longitudinal repeated-measures design to model the contribution of medication adherence to black-white differences in A1C among type 2 diabetic patients at a large multispecialty group practice. We identified 1,806 adult (aged Ն18 at diagnosis) patients (467 blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 26 publications
4
80
0
Order By: Relevance
“…In 1 study, longitudinal repeated measures design was used to model the contribution of medication adherence to BlackWhite differences in HbA1c in patients with type 2 diabetes. 10 Mean HbA1c at baseline was higher in Black and Blacks had lower medication adherence; however, adjust- ment for medication adherence did not eliminate the BlackWhite difference in HbA1c. In the Translating Research into Action study, glycemic control was lower in Blacks and adjustment for concerns about cost, trust in physicians, smoking, and physical inactivity did not diminish the observed racial/ethnic differences in glycemic control.…”
Section: Discussionmentioning
confidence: 95%
“…In 1 study, longitudinal repeated measures design was used to model the contribution of medication adherence to BlackWhite differences in HbA1c in patients with type 2 diabetes. 10 Mean HbA1c at baseline was higher in Black and Blacks had lower medication adherence; however, adjust- ment for medication adherence did not eliminate the BlackWhite difference in HbA1c. In the Translating Research into Action study, glycemic control was lower in Blacks and adjustment for concerns about cost, trust in physicians, smoking, and physical inactivity did not diminish the observed racial/ethnic differences in glycemic control.…”
Section: Discussionmentioning
confidence: 95%
“…Although one study (332) suggested that an important mediator of the association between minority status and poorer glycemic control was poorer adherence to medication among NHBs and Hispanic-Americans, other research did not find this association between race and adherence (335). The lack of consistent findings suggests that more work is needed to understand the causal pathways underlying disparities in diabetes control.…”
Section: Individual Risk Behaviorsmentioning
confidence: 87%
“…However, medication non-adherence is common and the benefit of the pharmaceutical therapy is discounted. A literature review indicated that of nine studies using objective measure of adherence such as medication possession ratio (MPR), seven found greater adherence was associated with improved glycemic control [9][10][11][12][13][14][15][16] ; of eight studies that evaluated hospitalization, seven showed higher adherences were associated with fewer hospitalizations 9 14 17-22 ; and of three studies that evaluated emergency department (ED) visits, two found higher adherences were associated with fewer visits. 9 17 19 In view of the chronic and progressive nature of diabetes, early medication intervention has the potential to optimize the glycemic control.…”
Section: Introductionmentioning
confidence: 99%